PERAN KONTEN VIDEO MUSIK DALAM MENINGKATKAN MOTIVASI INTRINSIK BELAJAR MUSIK PADA SANGGAR BIOLA QUINTA YOGYAKARTA - de Fretes, Daniel; Kartika, Hedwigis Nada Candra; Swara, Lintang Pramudia; Purwitasari, Nathalia Desy (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Due to rapid technological advances, innovation and creativity are necessary in every sector of life, including the world of arts education. This article aims to determine the role of music video content in increasing intrinsic motivation to learn music at Sanggar Biola Quinta Yogyakarta. Intrinsic motivation for learning music is an essential concept because the motive is built through habits that encourage students’ curiosity and high enthusiasm for music learning. Sanggar Biola Quinta Yogyakarta is a non-formal music education provider that is active in producing music video content on its YouTube channel. This research uses a qualitativemethod with a case study approach. Observation, documentation studies, and interviews carried out data collection. The research results show that the production of music video content in the form of violin solo cover videos on the Sanggar Biola Quinta YouTube channel plays a decisive role in increasing students’ intrinsic motivation to learn music, and increasing intrinsic motivation to learn music results in a high desire to study music more actively. The production of music video content that offers novelty in music learning tools at Sanggar Biola Quinta has a positive impact on student knowledge development.